Pelatihan Laporan Keuangan Pendidikan Pimpinan Cabang Muhammadiyah Setiabudi Pamulang Tangerang Selatan - M Nurrasyidin; Arif Widodo Nugroho; Fikri Hidayat (Faculty of Economics and Business, University of Muhammadiyah Prof. DR. HAMKA, 2020)
Financial reports are one of the important things in non-profit organizations such as churches, Islamic boarding schools, foundations, education and others, so in carrying out their vision, non-profit organizations still have to carry out financial management and make financial reports with a good and correct financial accounting system. Therefore, it is necessary to have adequate knowledge and skills training in making good and correct financial reports for school treasurers who are under the management of the Muhammadiyah Setiabudi Pamulang Branch Manager. This program is intended so that the treasurers of schools under the management of PCM Setiabudi Pamulang can master and make good and correct financial reports. Keywords: financial reports, education finance, education, treasurer